Constitutional illegitimacy over Brexit - Eleftheriadis, P (Wiley, 2017)
Members and supporters of the British government say that the only constitutionally legitimate course of action over Brexit after the referendum is to press ahead with withdrawal from the European Union, even if that would entail the complete severance of all ties (which we normally call ‘hard Brexit’). A more sophisticated view of the constitution, however, shows that these more or less populist arguments are false. As the Supreme Court confirmed in the recent Gina Miller judgment, the constitution did not change with the June referendum. Parliament is still supreme and determines both ordinary legislation and constitutional change. In fact, if one examines closely the claim that the referendum entails hard Brexit, it becomes obvious that this claim is false as well. The referendum opened the door for one among four different possibilities. Which Brexit option—if any—the United Kingdom should take is a matter for Parliament now to decide, following the normal processes of democratic deliberation and representation.